2018
DOI: 10.1111/pan.13471
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital usability and feasibility evaluation of Panda, an app for the management of pain in children at home

Abstract: Summary Background Postoperative pain in children is often poorly managed at home, leading to slower functional recovery, poor oral intake, sleep disturbances, and behavioral changes. Panda is a smartphone application (app) designed to support parents in assessing their child's pain and managing medications. Aims The aim of this study was to evaluate the Panda app's usability and feasibility in hospital prior to testing the app at home. Methods The study comprised two phases. Phase I evaluated Panda's usabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Besides, most manuscripts did not report on the measurement of effectiveness, efficiency, and satisfaction, because they fail to use a combination of methods that allows assessing these three domains [27]. Only eight out of the 31 manuscripts included [19,29,32,37,38,[54][55][56] assessed all the three domains of usability, despite existing recommendations to include measures of efficiency, effectiveness, and user satisfaction since a narrower selection of usability measures may lead to unreliable conclusions about the overall usability of the app [64]. Furthermore, there was an inconsistency between what was reported in the methodology section and the results presented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, most manuscripts did not report on the measurement of effectiveness, efficiency, and satisfaction, because they fail to use a combination of methods that allows assessing these three domains [27]. Only eight out of the 31 manuscripts included [19,29,32,37,38,[54][55][56] assessed all the three domains of usability, despite existing recommendations to include measures of efficiency, effectiveness, and user satisfaction since a narrower selection of usability measures may lead to unreliable conclusions about the overall usability of the app [64]. Furthermore, there was an inconsistency between what was reported in the methodology section and the results presented.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed analysis shows that all manuscripts, except one (out of 31) [51] assessed usability using appropriate procedures for the app development phase, but only two (out of 31) reported to have used an investigator adequately trained [35,40], and only one (out of 31) refers that the investigator responsible for usability assessment was external to the product development process [29]. Of the 31 manuscripts included, 11 used valid instruments to assess usability [19,29,31,[41][42][43]45,48,[55][56][57], but only nine triangulated methods of usability assessment [19,39,40,43,47,49,50,55,57]. The detailed results on the methodological quality assessment are presented in Table 2.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Panda sends periodic notifications to alert the patients to conduct a pain check and take medication. In a recent study, usability was improved and feasibility was demonstrated in the hospital setting …”
Section: Mhealth Programs For Pediatric Painmentioning
confidence: 99%
“…Panda sends periodic notifications to alert the patients to conduct a pain check and take medication. In a recent study, usability was improved and feasibility was demonstrated in the hospital setting 30. Children with illness, including cancer, also experience acute pain, which can occur repeatedly throughout the course of treatment.Accordingly, two promising mHealth interventions targeting pain during cancer treatment have been developed.…”
mentioning
confidence: 99%